PERILAKU KEWIRAUSAHAAN PENGUSAHA MEBEL DI DESA SUCO KECAMATAN MUMBULSARI KABUPATEN JEMBER - Ayu Putri Septiana; Sri Kantun; Retna Ngesti Sedyati (Economic Education, University of Jember, 2017)
The research is research qualitative descriptive aims to understand entrepreneurship furniture behavior businesses in Suco at Mumbulsari Jember. The subject in question are entrepreneurs furniture in the village Suco number four people. Data collection method used covering the observation, interviews and documents .The method of analysis the data used was descriptive the method qualitative described data-data obtained from the results of the field implementation. Research conducted through observation and interview, the results about behavior the entrepreneurial Suco village in Mumbulsari District Jember. Furniture businessmen in running their business always faced with the risk of trade that must be faced that the point is not her ways goods over been sold so that suffered losses or fortunately diminished. Entrepreneurs furniture always very sure with capability owned. To be able to survive and develop their business, furniture entrepreneurs do creativity and innovation to products that been sold. Furniture businessmen also noticed if the it has its consumers want to buy or ordering products, so that is not left by customers and it has its consumers